E-Buletin Arshad Ayub Graduate Business School, UiTM Shah Alam edisi Bil.6/2020 Julai - UiTM, Arshad Ayub Graduate Business School (Arshad Ayub Graduate Business School, 2020)
E-Buletin Arshad Ayub Graduate Business School, UiTM Shah Alam - July 2020.